KOMUNIKASI POLITIK KIAI NU DALAM KONTESTASI PILKADA PERSPEKTIF TEORI STRUKTURASI GIDDENS - Ubaidillah Nafi; Ishaq .; Pujiono . (Indonesian Journal of Islamic Communication, 2021)
This study raises the issue of political communication of kiai Nahdlatul Ulama (NU) in the contestation of regional head elections (Pilkada) and the agenda of developing civil society in Pasuruan Regency. Giddens' (1984) theory of structuration is used as a point of departure to develop key themes relevant to the data. The purpose of this research with the major theme of political communication is to understand the dialectical complexity between structure and agency that places the kiai (agent) as creative individuals and has the transformative capacity to produce and reproduce structures that on the one hand tend to limit (limiting-disable) and on the other hand, tend to be limiting. the other party enables (enabling) action, all of which is carried out by the kiai in his position as a political communicator of the religious elite for the development of civil society. This theme becomes interesting because there are many NU kiai who are directly or indirectly involved in the political map of the Pilkada that took place in this country. In fact, on one side of the organization, NU as a forum for the organization of the kiai has declared khithah as the paradigm of its struggle.